Syndrome or symptoms? Assessing cothymia, neuroticism and lifetime comorbidity in a sample of psychiatric patients - Fiammetta Iannuzzo; Fabiana Fiasca; Antonella Mattei; Carmela Mento; Maria Catena Silvestri; Fabrizio Turiaco; Rocco Antonio Zoccali; Maria Rosaria Anna Muscatello; Antonio Bruno (Journal of Mind and Medical Sciences)
Background. Cross-sectional and longitudinal psychiatric comorbidity rates could represent a syndromic process rather than the co-occurrence of different disorders. ‘Cothymia’, the concomitant presence of depression and anxiety symptoms, and the ‘neuroticism’ dimension have been proposed as candidate vulnerability factors for psychiatric disorders trajectories. Based on this background, the present research was aimed at assessing the role of cothymia and neuroticism as syndromic processes in lifetime psychiatric disorders, and examining homotypic or heterotypic trends in the diagnostic continuum of comorbid mental disorders. Materials and methods. Data collection was carried out retrospectively through the consultation of medical records at the Psychiatry Unit of the University Hospital of Messina. Cothymia was determined by the lifetime presence of depression and other anxiety disorders, and neuroticism was determined by the presence of borderline personality disorders and other personality disorders. Results. Cothymia and neuroticism were found in 580 patients with higher rates of hospitalization, drug prescription, polypharmacotherapy, and longer duration of illness. Furthermore, diagnostic trajectories in patients with cothymia and neuroticism followed both homotypic and heterotypic progressions. Limitations: This study presented several limitations. The small sample size from a restricted recruitment area, and the retrospective design may have influenced a realistic and accurate estimation of the lifetime prevalence of the disorders. Conclusions. Despite the limitations, the findings of this study confirm the presence of consistent and meaningful homotypic and heterotypic trajectories in psychiatric patients, suggesting that the evolution of lifetime diagnoses should become a focus in theoretical and practical approaches to psychiatric disorders.